Genome-wide Meta-analysis on the Sense of Smell Among US Older Adults. Issue 47 (November 2015) - Dong, Jing; Yang, Jingyun; Tranah, Greg; Franceschini, Nora; Parimi, Neeta; Alkorta-Aranburu, Gorka; Xu, Zongli; Alonso, Alvaro; Cummings, Steven R.; Fornage, Myriam; Huang, Xuemei; Kritchevsky, Stephen; et al.
Abstract : Abstract: Olfactory dysfunction is common among older adults and affects their safety, nutrition, quality of life, and mortality. More importantly, the decreased sense of smell is an early symptom of neurodegenerative diseases such as Parkinson disease (PD) and Alzheimer disease. However, the genetic determinants for the sense of smell have been poorly investigated. We here performed the first genome-wide meta-analysis on the sense of smell among 6252 US older adults of European descent from the Atherosclerosis Risk in Communities (ARIC) study, the Health, Aging, and Body Composition (Health ABC) study, and the Religious Orders Study and the Rush Memory and Aging Project (ROS/MAP). Genome-wide association study analysis was performed first by individual cohorts and then meta-analyzed using fixed-effect models with inverse variance weights. Although no SNPs reached genome-wide statistical significance, we identified 13 loci with suggestive evidence for an association with the sense of smell ( P meta  < 1 × 10 −5 ). Of these, 2 SNPs at chromosome 17q21.31 (rs199443 in NSF, P  = 3.02 × 10 −6 ; and rs2732614 in KIAA1267 – LRRC37A, P  = 6.65 × 10 −6 ) exhibited cis effects on the expression of microtubule-associated protein tau ( MAPT, 17q21.31) in 447 frontal-cortex samples obtained postmortem and profiled by RNA-seq ( P  < 1 × 10 −15 ). Gene-based and pathway-enrichment analyses further implicated MAPT in regulating the sense of smell in older adults. Similar results were obtained after excluding participants who reported a physician-diagnosed PD or use of PD medications. In conclusion, we provide preliminary evidence that the MAPT locus may play a role in regulating the sense of smell in older adults and therefore offer a potential genetic link between poor sense of smell and major neurodegenerative diseases. Abstract : Supplemental Digital Content is available in the text